Pembacaan Ulang Teori Pembelajaran Sosial Bandura sebagai Strategi Komunikasi dalam Konteks Pembelajaran Literasi Digital Lansia - Sarbani, Yohanes Adven; Satyawati, Niken Pupy; Lumakto, Giri; Teteki, Dwitasari B. (Fakultas Ilmu Komunikasi UKWMS, 2025)
Digital literacy is crucial for older adults to maintain independence and social connectedness. However, skill gaps, psychosocial barriers, and limited adaptive communication strategies hinder their participation. This article aims to develop a communication strategy framework based on Bandura’s Social Learning Theory to enhance elderly digital literacy learning. The study employs a targeted theoretical review of five relevant studies from Scopus, SpringerLink, Google Scholar, ScienceDirect, and DOAJ. The thematic synthesis identifies six key strategies: presenting relatable role models, providing verbal and emotional reinforcement, creating supportive learning environments, using real-life scenarios, strengthening outcome expectations, and applying personalized adaptive approaches. Each strategy is linked to Bandura’s core components: observational learning, modeling, and the strengthening of self-efficacy. Bandura's Social Learning Theory as a communication strategy is important in empowering the elderly to face the challenges of the digital world because it builds their intrinsic motivation to learn and strengthens their self-confidence. ABSTRAK Literasi digital menjadi kebutuhan krusial bagi lansia untuk mempertahankan kemandirian dan keterhubungan sosial. Namun, kesenjangan keterampilan, hambatan psikososial, dan keterbatasan komunikasi edukatif adaptif menghambat partisipasi mereka. Artikel ini bertujuan menyusun kerangka strategi komunikasi berbasis Teori Pembelajaran Sosial Bandura untuk memperkuat pembelajaran literasi digital lansia. Kajian dilakukan melalui targeted theoretical review terhadap lima studi relevan dari basis data Scopus, SpringerLink, Google Scholar, ScienceDirect, dan DOAJ. Analisis sintesis mengidentifikasi enam strategi utama: menghadirkan model sebagai teladan, penguatan verbal dan emosional, penciptaan lingkungan belajar yang mendukung, penggunaan skenario kehidupan nyata, penguatan outcome expectations, serta pendekatan personal dan adaptif. Setiap strategi terkait dengan komponen utama Bandura, yaitu observational learning, modeling, dan penguatan self-efficacy. Teori Pembelajaran Sosial Bandura sebagai strategi komunikasi menjadi penting dalam memberdayakan lansia dalam menghadapi tantangan dunia digital karena membangun motivasi intrinsik lansia untuk belajar dan memperkuat rasa percaya diri.